2022
DOI: 10.1177/00099228221139985
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of the Sleep Structure and Sleep Spindle Activity in Children With Primary Snoring and Sleep-Disordered Breathing

Abstract: Obstructive sleep apnea syndrome (OSAS) in children is associated with changes in the structure of sleep. The possible effects of snoring on spindle activity have not been established. We analyzed the polysomnography recordings and sleep spindle activity in children with primary snoring and/or OSAS compared with healthy children. Fifty-one children were included; 8 had primary snoring, 16 had OSAS and snoring, 11 had OSAS without snoring, and 16 were healthy controls. The density ( P = .034) and duration ( P =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…They found that the density and duration of sleep spindles were decreased in children with OSA compared with controls, but were not significantly different between children with primary snoring and healthy controls, or between children with OSA with/without snoring. These findings suggest that sleep spindle activity may be a more sensitive marker of sleep quality than snoring 15 …”
Section: Diagnosis Of Sdb: Beyond the Ahimentioning
confidence: 86%
See 2 more Smart Citations
“…They found that the density and duration of sleep spindles were decreased in children with OSA compared with controls, but were not significantly different between children with primary snoring and healthy controls, or between children with OSA with/without snoring. These findings suggest that sleep spindle activity may be a more sensitive marker of sleep quality than snoring 15 …”
Section: Diagnosis Of Sdb: Beyond the Ahimentioning
confidence: 86%
“…These findings suggest that sleep spindle activity may be a more sensitive marker of sleep quality than snoring. 15…”
Section: Polysomnographymentioning
confidence: 99%
See 1 more Smart Citation